Design and Development of a Web-Based Project Monitoring System Using the Prototype Method - Sherly Musva; Dian Ramadhani (Journal of Software Engineering and Multimedia (JASMED), 2025)
EMP Bentu Ltd – EMP Korinci Baru Ltd is a company operating in the natural gas sector and currently managing multiple on-site projects that require continuous monitoring. The project supervision process still relies on WhatsApp and email, resulting in fragmented communication, limited traceability of progress, and unstructured documentation management. These limitations hinder timely validation of vendor reports and complicate decision-making, highlighting the need for a centralized and systematic monitoring solution. This research aims to design and develop a web-based project monitoring system that provides real-time, structured, and integrated oversight of project activities. The Prototype development model was applied through iterative cycles consisting of requirement identification, rapid design, prototype construction, user evaluation, and refinement based on feedback. The resulting system integrates essential features such as project phase and activity management, vendor reporting modules, progress visualization through charts, a Gantt-based scheduling interface, and daily report approval workflows. System evaluation based on the ISO 25010 quality model demonstrates that the application improves the accuracy, accessibility, and timeliness of project monitoring across functional suitability, usability, performance efficiency, and security attributes. The implementation of this system is expected to enhance operational transparency and support faster, data-driven decision-making within the company. The study contributes a practical software solution tailored for energy-sector project environments, emphasizing the value of prototype-based development for user-centered system design.